Dispositivos de tecnologia assistiva para mobilidade: percepção das famílias de crianças com deficiências - Lima, Carolina Ferreira (Universidade Federal de São Carlos, 2024)
Mobility is closely linked to child development as it relates to how a child experiences their world, influencing their participation, play, and Activities of Daily Living, in addition factors such as self-esteem and social participation. This work was part of the initial stage of the project "AssistiVerse - Development of a Digital Platform for Personalization and Assistance in the Acquisition and Assembly of Assistive Mobility Devices." The objective was to understand the perception of families with children with disabilities regarding assistive technology devices for mobility, investigating their opinions and satisfaction with the equipment used. Methodology: This study is exploratory research with a qualitative nature. Data collection was conducted through an electronic form and Focus Groups to gather information about the participants and their history with the use of mobility devices. The goal was to actively involve participants in the identification of strengths and weaknesses in Assistive Technology (AT) products in the mobility category. Five family members of children diagnosed with Cerebral Palsy, aged between 0 and 10 years, participated in the study. The inclusion criterion was that the children should use some form of mobility aid, with no exclusions as all participating families met this criterion. Two remote Focus Groups were conducted, with one session per group and different participants in each. Three family members participated in the first group, and two in the second, with an average duration of sixty minutes per session. Parents were encouraged to discuss the topic based on their experiences, responding to prompting questions. The questions were divided into three blocks: advantages and benefits of using the device; weaknesses and challenging situations experienced; and requirements for new products. Results: Positive aspects identified by participants include adjustable settings, the presence of belts, and the foldable nature of some equipment. According to family members, acquiring these devices brought freedom for parents, reduced physical strain, improved postural adaptation for children, ease of movement in different spaces, and increased leisure activities. Negative aspects mentioned include the weight of wheelchairs, hindering transportation and handling, as well as difficulties in assembling and disassembling equipment with challenging fittings, fixed parts, and the need for specific tools. "Comfort" and "safety" were highlighted as crucial characteristics for caregivers in the development process, in addition to being foldable. Conclusions: Similarities in the participants' reports were observed, demonstrating the relevance of their observations and the potential value of user participation in the development of AT devices. The generated data can contribute to future projects involving device development, especially as Occupational Therapy's involvement with Assistive Technology has intensified, aiming at enhancing functional performance, independence, and social participation.
Assistive technology for mobility: perception of families children with disabilities
Keywords: Terapia ocupacional; Tecnologia assistiva; Limitação de mobilidade; Crianças com deficiência; Família; Occupational therapy; Assistive technology; Mobility limitation; Disabled children; Family; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL